The Establishment of an Ethical Guideline for Genetic Testing Through Citizen Consensus via the Internet in Taiwan - Lin, Chiou-Fen; Lu, Meei-Shiow; Chung, Chun-Chih; Yang, Che-Ming (JMIR Publications, 2010)
BackgroundWith the rapid advance of genetics, the application of genetic testing has become increasingly popular. Test results have had a tremendous impact on individuals who receive the test and his or her family. The ethical, legal, and social implications (ELSI) of genetic testing cannot be overlooked. The Internet is a potential tool for public engagement. ObjectivesThis study aimed at establishing ethical guidelines for genetic testing in Taiwan through a participatory citizen consensus approach via the Internet. MethodsThe research method used was a citizen consensus conference modified by an Internet application and the Delphi technique. The citizen consensus conference is one of the public participation mechanisms. The draft ethical guidelines for genetic testing were written by an expert panel of 10. The Delphi technique was applied to a citizen panel recruited via the Internet until a consensus was reached. Our research population was restricted to people who had Internet access. ResultsIncluded in the citizen panel were 100 individuals. A total of 3 individuals dropped out of the process. The citizen panel was exposed to the issues through Internet learning and sharing. In all, 3 rounds of anonymous questionnaires were administered before a consensus was reached in terms of importance and feasibility. The result was ethical guidelines composed of 4 categories and 25 items. The 4 categories encompassed decision making (6 items), management of tissue samples (5 items), release of results (8 items), and information flow (6 items). On a scale of 1 to 10, the average (SD) importance score for the decision-making category was 9.41 (SD 0.58); for the management of tissue samples category, the average score was 9.62 (SD 0.49); for the release of results category, the average score was 9.34 (SD= 0.59); and for the information flow category, the average score was 9.6 (SD = 0.43). Exploratory analyses indicated that participants with higher education tended to attribute more importance to these guidelines. ConclusionsThe resulting recommended ethical guidelines had 4 categories and 25 items. We hope through the implementation of these guidelines that mutual trust can be established between health care profession and the general public with respect to genetic tests.